Taskforces: a cure for all ills? Policy advisory systems in times of polycrises - Céline Mavrot; Caroline Schlaufer; Johanna Hornung; Fritz Sager; Caspar Hirschi; Dylan Jaton (Policy Design and Practice)
This article explores the flourishing claims to create crisis taskforces in the wake of the COVID-19 pandemic. Are taskforces a remedy for all crises? Taskforces are ad-hoc created groups of highly specialized experts who provide advice to policymakers. They have the advantages of flexibility and allow to recruit high-level competences for short-term mandates. However, taskforces are not a panacea, as different types of crises (e.g. creeping crises, disruptive events, cyclical crises) require different types of policy advisory systems. A taskforce is also a short-term, reactive model, which runs the risk of politicization. This article analyzes the suitability of the taskforce model in various situations and compares expert advice provided to decision-makers during the financial crisis and during the COVID-19 pandemic in Switzerland. It answers the question of what types of advisory systems suit what type of crisis. The contribution shows that in the era of polycrises, one size does not fit all and the distinctive characteristics of crises must be considered to find a fit-for-purpose approach.